2009
DOI: 10.1038/onc.2009.62
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation inhibits p53-mediated survivin repression

Abstract: The molecular progression of endometrial cancer is poorly understood, and both genetic and epigenetic factors play a role. Survivin is a member of the inhibitor of apoptosis (IAP) gene family and contains a canonical CpG island that has been described as epigenetically regulated. As survivin is overexpressed in endometrial tumors, we hypothesized that hypomethylation could explain this expression pattern. Surprisingly, methylation-specific PCR and pyrosequencing showed that survivin was hypermethylated in endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 29 publications
3
74
0
Order By: Relevance
“…In a previous study, we observed p53-dependent repression of NEK2 following treatment with 5aza-dC (8). Here, we report that NEK2 is repressed by wild-type p53 and that loss of p53 results in local accumulation of DNA methylation.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…In a previous study, we observed p53-dependent repression of NEK2 following treatment with 5aza-dC (8). Here, we report that NEK2 is repressed by wild-type p53 and that loss of p53 results in local accumulation of DNA methylation.…”
supporting
confidence: 51%
“…Additional RT-qPCR primer sequences are listed in supplemental Table 1. The assays were performed at the Quantitative Genomics Core Laboratory (University of TexasHouston Medical School) using a 7700 Sequence Detector (Applied Biosystems) as described previously (8). Transcripts were quantified using the ⌬⌬Ct method, normalizing to 18 S rRNA or ␤-actin mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24] Such a mechanism of de-repression as a result of epigenetic regulation by DNA methylation has recently been shown for survivin. 51 In this study, methylation of survivin promoter inhibits the binding of p53, a repressor of its expression. In keeping, earlier studies showed that methylation of the hTERT promoter at the CTCF-binding site inhibited the binding of CTCF, thus derepressing hTERT in some human tumors.…”
Section: Discussionmentioning
confidence: 76%
“…This in vivo binding preference is supported by a recent study which showed that in endometrial tumor samples, CGI promoter methylation at survivin/BIRC5 prevented p53 from binding. 66 Cancer development is known to be associated with substantial epigenetic changes, DNA hypomethylation on in IMR90, their distributions remain clearly different from the cancer data sets (Fig. S8).…”
Section: Resultsmentioning
confidence: 92%